Calculations of stopping powers of 100 eV to 30 keV electrons in 10 elemental solids - Tanuma, S.; Powell, C. J.; Penn, D. R. (Surface and interface analysis, 2005)
We present calculated electron stopping powers (SPs) for 10 elemental solids (Al, Si, Cr, Ni, Cu, Ge, Pd, Ag, Pt, and Au). These calculations were made for electron energies between 100 eV and 30 keV, and were obtained using the same basic algorithm as that employed in our previous calculations of electron inelastic mean free paths. We present comparisons of these results with measured values, with results of other calculations, with the nonrelativistic Bethe SP equation, and with the empirical modification of the Bethe equation by Joy and Luo. We find generally satisfactory agreement of our calculated SPs with measured values for some solids (Ni, Cu, Pd, and Pt) and limited agreement for others (Al, Si, Cr, Ge, and Ag). Our SPs for Al, Cu, Ag, and Au are systematically greater than those calculated by Ashley by up to 33% for E < 10 keV; these differences are associated with an exchange correction made in Ashley's calculations, but not in ours. We find close agreement between our SPs for Al, Si, and Cu and those calculated by Fernandez‐Varea et al. who included an exchange correction; larger differences, however, were found for Au. As expected, our calculated SPs agree with values from the Bethe equation only for energies above 10 keV (for Z ≤ 32) and about 30 keV for Z ≥ 46. Satisfactory agreement is found between our SPs and values from the Joy and Luo equation for Al, Si, Cr, Ni (for energies above 1 keV), Cu, and Ge but there is less agreement for Pd and appreciable disagreement for Au. We present an analysis of our calculated SPs for Al that show why the Bethe equation is not expected to be valid unless the electron energy is larger than about 10 keV. Copyright © 2005 John Wiley & Sons, Ltd.